Penatalaksanaan Holistik Pasien Laki-laki Berusia 49 Tahun dengan Demam Berdarah Dengue Melalui Pendekatan Kedokteran Keluarga - Sharlene Sabrina Azzahra (Utan Kayu Publishing, 2022)
Dengue hemorrhagic fever (DHF) is an acute viral infectious disease caused by the dengue virus which in general can be characterized by symptoms of fever for 2-7 days, accompanied by other symptoms in the form of bleeding, such as nosebleeds and red spots on the body (ptekiae), bleeding gums, decreased platelets, the form of hemoconcentration in the form of plasma leakage with signs such as increased hematocrit, ascites, pleural effusion. This journal is to Implementing family doctor services by identifying risk factors, clinical problems, and patient management based on Evidence-Based Medicine that is family-approach, patient-centred and community-oriented. The study conducted is a case report. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from the patient's medical records at the puskesmas. Assessment is carried out based on a holistic diagnosis from the beginning, process, and end of the study quantitatively and qualitatively. The patient is a 49 year old male, with complaints of fever that has been felt since 3 days ago. Complaints of fever followed by complaints of weakness, joint and muscle pain, also accompanied by bleeding gums and nausea and vomiting. Several factors can affect the patient's condition, namely internal and external risk factors. In this case, diagnosis and treatment have been carried out according to the latest theory and journals. After the intervention, there was a decrease in clinical symptoms and an increase in the knowledge of patients and their families. The diagnosis of dengue hemorrhagic fever in this patient was in accordance with the theory from several guidelines and journals, it was seen that there was a change in knowledge of the patient and his family after an intervention based on Evidence-Based Medicine that was patient-centred and a family approach. Abstrak: Demam berdarah dengue (DBD) merupakan salah satu penyakit infeksi virus akut yang disebabkan oleh virus dengue yang secara umum dapat ditandai dengan gejala demam selama 2-7 hari, disertai pula dengan adanya gejala lain dalam bentuk perdarahan, seperti mimisan, bintik-bintik merah pada tubuh, gusi berdarah; penurunan trombosit, adanya bentuk hemokonsentrasi berupa kebocoran plasma dengan tanda-tanda seperti peningkatan hematokrit, asites, efusi pleura. Penelitian ini menerapkan pelayanan dokter keluarga dengan mengidentifikasi faktor risiko, masalah klinis, serta penatalaksanaan pasien berbasis Evidence-Based Medicine yang bersifat family-approach, patient-centred dan community oriented. Studi yang dilakukan adalah laporan kasus. Data primer diperoleh melalui anamnesis, pemeriksaan fisik dan kunjungan ke rumah. Data sekunder didapat dari rekam medis pasien di puskesmas. Penilaian dilakukan berdasarkan diagnosis holistik dari awal, proses, dan akhir studi secara kuantitatif dan kualitatif. Pasien laki-laki berusia 49 tahun, dengan keluhan demam sejak 3 hari yang lalu. Keluhan demam diikuti dengan keluhan lemas, nyeri sendi dan nyeri otot, juga disertai perdarahan gusi dan mual muntah. Beberapa faktor dapat memengaruhi keadaan pasien yaitu faktor risiko internal dan eksternal. Pada kasus ini telah dilakukan diagnosis dan tatalaksana sesuai dengan teori dan jurnal terkini. Setelah dilakukan intervensi, didapatkan penurunan gejala klinis dan peningkatan pengetahuan pasien dan keluarganya. Diagnosis demam berdarah dengue pada pasien ini sudah sesuai dengan teori dari beberapa panduan dan jurnal, terlihat adanya perubahan pengetahuan pada pasien dan keluarganya setelah dilakukan intervensi berdasarkan Evidence-Based Medicine yang bersifat patient-centred dan family approach.